2016
DOI: 10.4049/jimmunol.1502232
|View full text |Cite
|
Sign up to set email alerts
|

PSM Peptides of Staphylococcus aureus Activate the p38–CREB Pathway in Dendritic Cells, Thereby Modulating Cytokine Production and T Cell Priming

Abstract: The challenging human pathogen Staphylococcus aureus has highly efficient immune evasion strategies for causing a wide range of diseases, from skin and soft tissue to life-threatening infections. Phenol-soluble modulin (PSM) peptides are major pathogenicity factors of community-associated methicillin-resistant S. aureus strains. In previous work, we demonstrated that PSMs in combination with TLR2 ligand from S. aureus induce tolerogenic dendritic cells (DCs) characterized by the production of high amounts of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 46 publications
0
31
0
1
Order By: Relevance
“…17 Formyl peptide receptors belong to a family of transmembrane G protein-coupled receptors that regulate the production of angiogenic and inflammatory factors through the modulation of transcription factors including hypoxia-inducible factor (HIF)-1, signal transducer and activator of transcription factor 3 (STAT3), nuclear factor kB (NF-kB), and cAMP response element binding protein (CREB). [18][19][20] Among peptide inhibitors of uPAR, the tetrapeptide Ac-L-Arg-Aib-L-Arg-L-Ca(Me)Phe-NH 2 , named UPARANT, displays lasting resistance to enzymatic digestion and high stability in blood and plasma; it strongly inhibits endothelial cell migration and proliferation by interfering with the complex cross talk between uPAR and FPRs. 21 In vitro, UPARANT reduces capillary sprout formation, whereas in vivo, it inhibits VEGFinduced vascularization in a rabbit corneal pocket assay and recovers retinal neovascularization, inner BRB leakage, and visual dysfunction in a mouse model of oxygen-induced retinopathy (OIR).…”
mentioning
confidence: 99%
“…17 Formyl peptide receptors belong to a family of transmembrane G protein-coupled receptors that regulate the production of angiogenic and inflammatory factors through the modulation of transcription factors including hypoxia-inducible factor (HIF)-1, signal transducer and activator of transcription factor 3 (STAT3), nuclear factor kB (NF-kB), and cAMP response element binding protein (CREB). [18][19][20] Among peptide inhibitors of uPAR, the tetrapeptide Ac-L-Arg-Aib-L-Arg-L-Ca(Me)Phe-NH 2 , named UPARANT, displays lasting resistance to enzymatic digestion and high stability in blood and plasma; it strongly inhibits endothelial cell migration and proliferation by interfering with the complex cross talk between uPAR and FPRs. 21 In vitro, UPARANT reduces capillary sprout formation, whereas in vivo, it inhibits VEGFinduced vascularization in a rabbit corneal pocket assay and recovers retinal neovascularization, inner BRB leakage, and visual dysfunction in a mouse model of oxygen-induced retinopathy (OIR).…”
mentioning
confidence: 99%
“…We also investigated the mechanisms underlying the cytokine production by studying kinetics of activation of MAPK p38 and NF-kB p65 pathways (Figure 5), known regulators of S. aureus -induced immune response (Krishna and Miller, 2012; Armbruster et al, 2016). We observed that wt USA300 and esx mutants stimulate intracellular MAPK and NF-kB activation with different kinetics and to a different extent.…”
Section: Discussionmentioning
confidence: 99%
“…The MAP kinases, such as p38, have been reported to act as upstream kinases mediating CREB phosphorylation at Ser133 [29, 30]. We, therefore, investigated the effect of p100 on MAPK and their upstream kinase activation.…”
Section: Resultsmentioning
confidence: 99%